Fillers in EFL Students’ Spoken Analytical Exposition at SMA Negeri 3 Semarang - Pratama, Nathanael Joan; Yuliati (PROJECT (Professional Journal of English Education), 2026)
Speaking fluency is one of challenges for EFL students, particularly in spontaneous spoken. To address these challenges, students often employ fillers as communicative strategies. This research aims to explore the types and functions of fillers applied by EFL students in short spoken analytical exposition at SMA Negeri 3 Semarang. This research applied a qualitative approach with limited frequency counts. The data consists of 30 video recordings of speaking performances produced by 60 eleventh-grade students and were transcribed verbatim. The fillers’ types were classified according to Rose (1998), while their functions were analyzed using Stenstrom’s (1994) framework. The findings revealed a total of 91 fillers, with unlexicalized fillers being the most dominant. This dominance indicates students’ preference for immediate and low-effort strategies when facing linguistic constraints during spontaneous speech. Furthermore, the fillers served five communicative functions: hesitation devices, time-creating devices, empathizing devices, mitigating devices, and editing terms. These results confirm that fillers functioned as strategic resources in spoken language rather than as indicators of low proficiency. Fillers play a significant role in supporting EFL students’ fluency, discourse management, and interactional competence. Therefore, this study suggests that fillers should be pedagogically recognized and integrated into speaking instruction to enhance students’ communicative strategies.